Martin Luther in Rom Die Ewige Stadt als kosmopolitisches Zentrum und ihre Wahrnehmung - Matheus, Michael; Nesselrath, Arnold; Wallraff, Martin (Bibliothek des Deutschen Historischen Instituts in Rom, 2017)
About 500 years ago, Martin Luther visited Rome. Reflections about his journey often inquire as to its having been a critical factor for the Reformation, a prejudicial perspective often leading to a negative view of the trip and the city. The volume seeks to free up the theme from this paradigm, and to impart a differentiated picture of the city of Rome, Luther`s Roman journey, and the recollected images associated with it.